The Weekend Pastor: A Christian Spirituality Analysis from the context of the GKI Kemtuk Gresi in Papua - Kathleen Grace Noya; Stefanus Christian Haryono (ARUMBAE: Jurnal Ilmiah Teologi dan Studi Agama, 2025)
This article aims to discuss the meaning of the calling as a pastor in the context of the GKI Kemtuk Gresi in Papua. A pastor is called and sent by God to serve the congregations. Service to the congregation is holistic, encompassing all dimensions of human life. However, this service cannot be fully implemented if the pastor is not in the midst of the congregation's struggles full time. This study discusses the phenomenon of weekend pastors, who visit the congregation only on Saturdays and Sundays. With a qualitative approach and using a holistic and transformative Christian spirituality perspective, this study describes the reality of weekend pastors, and constructs the concept of a pastor's spirituality. The study revealed that love for the calling is the main foundation that supports pastors amidst the pressures of ministry. However, separation from family, emotional exhaustion, and lack of support from the church community can erode this sense of calling. Thus, pastor spirituality must be fostered holistically, including relationships with God, self, family, and congregation. Referring to the insights of Henri Nouwen and Flora Slosson Wuellner, this article emphasizes the need for soul care, inner healing, and community support to maintain authentic and liberating ministry. Holistic and transformative spirituality not only prevents spiritual burnout but also strengthens the transformative impact of ministry on the lives of the congregation.